Imagens do labor : memória e esquecimento nas fotografias do trabalho da antiga metalúrgica Abramo Eberle (1896-1940) - Tessari, Anthony Beux (2013)
This study aims to analyze a set of 107 photos from an album produced by photographic Metalúrgica Abramo Eberle, factory founded by an Italian immigrant in the city of Caxias do Sul, State of Rio Grande do Sul. The album in question is responsible for construct a visual narrative of the history of the company, containing images that refer to various stages of their development. Because of this, we seek to understand the album as a storage medium being the same, responsible for the construction of a particular company's past (or rather, a "formalized last"). Moreover, because of the recurring themes in more visual support, the photos to be analyzed allow us to rebuild a significant part of the history of local labor, based on the Metalúrgica Abramo Eberle, that this was one of the largest companies of its kind in South America. The album art cover a period between the years 1896 and 1940.